Child Sexual Abuse and Adult Mental Health, Sexual Risk Behaviors, and Drinking Patterns Among Latino Men Who Have Sex With Men. Issue 3 (3rd April 2018) - Levine, Ethan Czuy; Martinez, Omar; Mattera, Brian; Wu, Elwin; Arreola, Sonya; Rutledge, Scott Edward; Newman, Bernie; Icard, Larry; Muñoz-Laboy, Miguel; Hausmann-Stabile, Carolina; Welles, Seth; Rhodes, Scott D.; et al.
ABSTRACT: One in five Latino men who have sex with men has experienced child sexual abuse. Although concerning in itself, child sexual abuse may increase an individuals' likelihood of depression and risk-taking in adult life, including engagement in HIV risk behaviors and alcohol and substance use. It is therefore urgent that researchers and practitioners better understand the long-term effects of child sexual abuse. We utilized logistic and linear regression to assess associations between child sexual abuse (operationalized as forced or coerced sexual activity before age 17) and depression, sexual behaviors, and drinking patterns in a sample of 176 adult Latino men who have sex with men from New York City. Over one-fifth (22%) of participants reported child sexual abuse. In multivariable models, participants with histories of child sexual abuse were significantly more likely than participants without such histories to screen for clinically significant depressive symptoms and heavy drinking and reported more anal sex acts, male sexual partners, and incidents of condomless anal intercourse in the previous three months. These findings confirm a high prevalence of child sexual abuse among Latino men who have sex with men and associations between child sexual abuse and adulthood depressive symptoms, high-risk alcohol consumption, and sexual risk behaviors. We recommend that providers who serve Latino men who have sex with men incorporate child sexual abuse screenings into mental health, HIV prevention, and substance use treatment programs, utilizing approaches that are inclusive of resilience.